Long-term real-world evidence of CPX-351 of high-risk patients with AML identified high rate of negative MRD and prolonged OS - Thomas Cluzeau; Fabio Guolo; Edmond Chiche; Paola Minetto; Ramy Rahme; Sarah Bertoli; Luana Fianchi; Jean-Baptiste Micol; Michele Gottardi; Pierre Peterlin; Sara Galimberti; Xavier Thomas; et al. (Blood Advances)
Abstract: CPX-351 has been approved for patients with therapy-related acute myeloid leukemia (t-AML) or AML with myelodysplasia-related changes (MRC-AML). No extensive data are available on measurable residual disease (MRD) and long-term clinical outcome using CPX-351 in AML in real life. We retrospectively collected data from 168 patients in 36 centers in France and Italy who had received 1 or 2 cycles of induction with CPX-351. All patients were aged >18 years and had newly diagnosed, untreated t-AML or MRC-AML. With a median follow-up of 3 years, the median overall survival (OS) was 13.3 months. The median OS was 20.4 months vs 12.9 months for patients with MRD below or above 10–3, respectively (P = .006). In a multivariate analysis, only MRD >10–3 was associated with a poorer OS (hazard ratio, 2.6; 95% confidence interval, 1.2-5.5; P = .013). We also observed a trend toward a better median OS in patients who underwent hematopoietic stem cell transplantation with MRD <10–3 (not reached vs 26.0 months; P = .06). Achievement of MRD negativity contributed to the improvement of OS in the overall population and, maybe, in patients receiving transplant. These data provide the rationale for the 2 ongoing studies evaluating CPX-351 vs 7+3 in non–MRC-AML and non–t-AML using MRD as the primary end point for ALFA-2101 phase 2 clinical trial and event-free survival for AMLSG 30-18 phase 3 clinical trial.